2017
DOI: 10.1088/2057-1976/aa91f9
|View full text |Cite
|
Sign up to set email alerts
|

Conductive gelatin methacrylate-poly(aniline) hydrogel for cell encapsulation

Abstract: New conductive hydrogels with superior biocompatibility continue to be developed in order to serve as bioactive scaffolds capable of modulating cellular functionality for tissue engineering applications. We developed an electrically conductive gelatin methacrylate-poly(aniline) (GelMA-PANi) hydrogel that is permissive of matrix mineralization by encapsulated osteoblast-like cells. Incorporation of PANi clusters within the GelMA matrix increases the electro-conductivity of the composite gel, while maintaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The addition of HUVECS alongside the Saos-2 cells in the bulk matrix resulted in the deposition of mineral within the center of our constructs between the two perfusable channels. Previous studies with Saos-2 cells encapsulated within GelMA hydrogels have shown that there is a diffusion limitation at the center of the hydrogel that inhibits mineral deposition [ 58 , 59 ]. This previously observed inhibition is reinforced by observation of in vivo tissue architecture that shows most cells reside within 100–200 μm of a nutrient supply, which allows for normal physiologic function [ 15 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of HUVECS alongside the Saos-2 cells in the bulk matrix resulted in the deposition of mineral within the center of our constructs between the two perfusable channels. Previous studies with Saos-2 cells encapsulated within GelMA hydrogels have shown that there is a diffusion limitation at the center of the hydrogel that inhibits mineral deposition [ 58 , 59 ]. This previously observed inhibition is reinforced by observation of in vivo tissue architecture that shows most cells reside within 100–200 μm of a nutrient supply, which allows for normal physiologic function [ 15 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…GelMA, a denatured form of collagen, was chosen as model hydrogel due to its widespread use in the field and due to established synthesis, fabrication, and material characterization techniques. 12,35,36 Saos-2, an osteoblast-like cell line, was chosen as it is a widely used cell line that deposits mineral within hydrogel matrix when chemically stimulated, mimicking the process of mineral deposition occurring in vivo. 9,12,35 Bright-field images taken on day 7 showed that the initial deposition of mineral resulted in the formation of isolated aggregates that merged and formed a continuous and partially connected unit with increasing culture durations (days 14, 21, and 28).…”
Section: Discussionmentioning
confidence: 99%
“…12,35,36 Saos-2, an osteoblast-like cell line, was chosen as it is a widely used cell line that deposits mineral within hydrogel matrix when chemically stimulated, mimicking the process of mineral deposition occurring in vivo. 9,12,35 Bright-field images taken on day 7 showed that the initial deposition of mineral resulted in the formation of isolated aggregates that merged and formed a continuous and partially connected unit with increasing culture durations (days 14, 21, and 28). This provides an explanation of why mineralized constructs on day 7 had compressive moduli closer to the day 1 constructs, as isolated mineral deposits randomly within the GelMA matrix were unable to provide additional resistance against compressive loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Furthermore, GelMA is capable of being UV crosslinked with minimal negative side effects to the encapsulated cells and their properties have shown consistency between batches. 5,[24][25][26][27] B. Optimization of process parameters…”
Section: A Device Fabricationmentioning
confidence: 99%